China's gteat train : Beijing's drive west and the campaign to remake Tibet - Lustgarten, Abraham (New York : Times Books, 2009)
In the summer of 2006, the Chinese government fulfilled a fifty-year plan to build a railway into Tibet. Since Mao Zedong first envisioned it, the line had grown into an imperative, a critical component of Chinas breakneck expansion and the final maneuver in strengthening Chinas grip over this remote and often mystical frontier, which promised rich resources and geographic supremacy over South Asia. Through the lives of the Chinese and Tibetans swept up in the project, Fortune magazine writer Abrahm Lustgarten explores the Wild West atmosphere of the Chinese economy today. He follows innovative Chinese engineer Zhang Luxin as he makes the trains route over the treacherous mountains and permafrost possible (for now), and the tenacious Tibetan shopkeeper Rinzen, who struggles to hold on to his business in a boomtown that increasingly favors the Han Chinese. As the railwaythe highest and steepest in the worldextends to Lhasa, and Chinas Go West campaign delivers waves of rural poor eager to make their fortunes, their lives and communities fundamentally change, sometimes for good, sometimes not. Lustgartens book is a timely, provocative, and absorbing first-hand account of the Chinese boom and the promise and costs of rapid development on the countrys people.
Now is the time -- A sometime Buddhist -- A bigger stage -- Stray dogs -- Moving heaven and earth -- Free Tibet -- Under a Han sun -- The gambler -- The race to reach Lhasa -- Paradise rebuilt -- When the Wang family came to town -- Hu's west
Includes bibliographical references (p. 289-293) and index
Keywords: Railroads -- China -- Tibet -- History -- 20th century; Transportation policy -- China; Tibet (China) -- Relations -- China; China -- Relations -- China -- Tibet